2022
DOI: 10.3390/agronomy12112638
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Mineral and Organo-Mineral Nitrogen Fertilization and the Role of Amino Acids as Plant Growth Promoters in Maize Cultivation

Abstract: The challenge to increase nitrogen uptake efficiency in intensively cultivated soils without runoffs and atmospheric release has been difficult to handle and usually leads to the excess application of mineral fertilizers. In the present study, four combinations of two different N fertilizers and a control were used in maize cultivation to evaluate the use of different types of N fertilization in the case of agronomic and plant physiology characteristics, as well as the quantity and quality characteristics of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…This was confirmed by Księ żak et al, who found an increasing effect on protein content in soybean, which was significantly increased by about 14% compared to non-fertilized soybean [43]. Efthimiadou et al reported the same fat and protein results after applying various concentrations of N fertilizer treatments, with the protein content varying between 6.39% and 6.71% and fat between 2.93% and 3.0% [44]. The fat levels in maize with fertilizer applied were significantly different, ranging from 3.86% to 4.61% (control 3.42%), and in soybean, they ranged from 19.22% to 22.85% (control 19.09%).…”
Section: Effects Of Different Fertilizers On Maize and Soybean Qualitymentioning
confidence: 59%
“…This was confirmed by Księ żak et al, who found an increasing effect on protein content in soybean, which was significantly increased by about 14% compared to non-fertilized soybean [43]. Efthimiadou et al reported the same fat and protein results after applying various concentrations of N fertilizer treatments, with the protein content varying between 6.39% and 6.71% and fat between 2.93% and 3.0% [44]. The fat levels in maize with fertilizer applied were significantly different, ranging from 3.86% to 4.61% (control 3.42%), and in soybean, they ranged from 19.22% to 22.85% (control 19.09%).…”
Section: Effects Of Different Fertilizers On Maize and Soybean Qualitymentioning
confidence: 59%